Egg Production and Bone Stability of Local Chicken Breeds and Their Crosses Fed with Faba Beans - Nolte, Tanja; Jansen, Simon; Halle, Ingrid; Scholz, Armin Manfred; Simianer, Henner; Sharifi, Ahmad Reza; Weigend, Steffen (Animals (Basel), 2020)
Poultry production is raising concerns within the public regarding the practice of culling day-old chicks and the importation of soy from overseas for feedstuff. Therefore, an alternative approach to poultry production was tested. In two consecutive experiments, two traditional chicken breeds, Vorwerkhuhn and Bresse Gauloise, and White Rock as a commercial layer genotype as well as crossbreds thereof were fed diets containing either 20% vicin-rich or vicin-poor faba beans, though addressing both subjects of debate. Hen performance traits and bone stability were recorded. All parameters were considerably influenced by the genotype with White Rock showing the significantly highest (p < 0.05) laying performance (99.4% peak production) and mean egg weights (56.6 g) of the purebreds, but the lowest bone breaking strength (tibiotarsus 197.2 N, humerus 230.2 N). Regarding crossbreds, the Bresse Gauloise × White Rock cross performed best (peak production 98.1%, mean egg weight 58.0 g). However, only limited dietary effects were found as only the feeding of 20% vicin-rich faba beans led to a significant reduction of egg weights of at most 1.1 g (p < 0.05) and to a significant reduction of the shell stability in the crossbred genotypes. In terms of dual-purpose usage, crossing of Bresse Gauloise with White Rock seems to be the most promising variant studied here.